1994
DOI: 10.2519/jospt.1994.20.6.302
|View full text |Cite
|
Sign up to set email alerts
|

Interdevice Reliability and Validity Assessment of the Nicholas Hand-Held Dynamometer

Abstract: , MS, LPT3 Kara M. long, MS, lP7" Neil B. Meske, MS, lPT5 M easurement of muscle strength is a basic but integral part of the physical assessment of patients. The evaluation of musclk strength is accomplished using a number of methods, ranging from manual muscle testing (MMT) to the use of sophisticated isokinetic dynamometry. Although MMT is the oldest and most commonly used technique to assess muscle strength, it is based on a system of grading movement against the examiner's resistance or resistance pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 16 publications
2
58
0
2
Order By: Relevance
“…Many previous studies 8, [16][17][18][19][20][21] have reported lower measured values with HHD compared with IKD (Table 3). Measurements of muscle strength of the lower limbs reported in these previous studies were not conducted on healthy male subjects, which could explain why the measured values reported in those studies were lower than the measured values obtained in this study.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Many previous studies 8, [16][17][18][19][20][21] have reported lower measured values with HHD compared with IKD (Table 3). Measurements of muscle strength of the lower limbs reported in these previous studies were not conducted on healthy male subjects, which could explain why the measured values reported in those studies were lower than the measured values obtained in this study.…”
Section: Discussionmentioning
confidence: 82%
“…In hip abduction, the correlation coefficient when two subjects with high measurements were excluded was r=0.51. The range of correlation coefficients in previous research 8,[16][17][18][19][20][21] comparing measurements obtained using HHD and IKD is from 0.519 to 0.93 (Table 3). Therefore, we consider the validity of muscle strength measurements of the hips and lower limbs using a HHD and belt fastened to an anchor point, based on the validity of methods using IKD, to be similar to when measurement is made with an HHD fastened to the examiner's hand, except when the measured values for hip adduction using an IKD is 500 N or greater.…”
Section: Discussionmentioning
confidence: 92%
“…The non-operated knee was always evaluated first. This procedure is known to be valid and reliable (63)(64)(65)(66)(67)(68)(69)(70). Furthermore, this procedure was shown to have very good to excellent intra-and interrater reliability with ICC Ͼ 0.87 (71).…”
Section: Personal Variablesmentioning
confidence: 92%
“…The reliability of this tool was already shown. 26 The highest value recorded between the two legs for quadriceps strength was used in this analysis. 27 The cutoffs for leg extension were 22.7 and 33.6 kg in men, and 16.4 and 23.5 kg in women;…”
Section: A Physical Performance Testsmentioning
confidence: 99%